Effect Of Leaves Extract Of Indigenous Species Of Syzygium Cumini On Dental Caries Causing Pathogens - LUBNA TAHIR,; SAFIA AHMED,; NAQI HUSSAIN,; IRUM PERVEEN,; SALMA RAHMAN, (International Journal of Pharma and Bio Sciences, 2012)
Dental caries is a common disease that results in tooth loss or cavitations. Medicines available in market though effectively treat dental caries but not without imparting the harmful effects. Medicinal plants have proven to be an effective and safe alternative to synthetic medicines. In vitro antibacterial activity of leaves of Syzygium cumini was studied against Streptococcus viridans, Streptococcus mutans, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis. The aqueous, methanolic, hexane and ethyl acetate extract of leaves of S. cumini exhibited the antimicrobial activity against dental caries causing strains. The largest zone of inhibition was obtained with the methanolic extract against E. coli (20mm). Minimum Inhibitory Concentration (MIC) of extract was also determined against the selected microorganisms showing zone of inhibition ≥ 8mm.The study concluded that the leaves of S. cumini possessed very good antibacterial activity against dental caries causing microorganisms and can be used as a potential source for making a phytomedicine that can be used to cure dental caries.